Faktor-Faktor yang Memengaruhi Stress pada Anak Thalasemia Bergantung Transfusi - Munifah, Laelatul; Agsutini, Nur; Rachmawati, Imami Nur (Journal of Telenursing (JOTING), 2024)
This study aims to determine the factors influencing stress in children with transfusion-dependent thalassemia. The method used in writing this article is a systematic review. This article was written using a database owned by the University of Indonesia through lib. UI is a website that facilitates students' search for literature. Eight databases were used to write the systematic review in this article, namely Proquest, ScienceDirect, Pubmed, Scopus, EMBASSE, EBSCO, Taylor & Francis Online, and SpringerLink, and used the "Reporting Items for Systematic Reviews and Meta-Analysis Flow Diagram" (PRISMA) guidelines. The research results show that factors that influence stress in transfusion-dependent thalassemia children include age, frequency of transfusions, onset of chelation therapy, duration of illness, body image, self-confidence, complications of the disease, hemoglobin (Hb), and ferritin levels. In conclusion, factors that can cause stress in children with thalassemia can be complications of the disease, age, gender, and duration. Keywords: Pediatric, Stress, Thalassemia